Medical Chatbot Using Sequence Modelling in Machine Learning - Kumar, S Nithish; Sujatha, S (International Journal of Computer Sciences and Engineering, 2023)
This project is focused on building a sophisticated chatbot that makes use of cutting-edge Natural Language Processing (NLP) methods to create seamless communication between users and healthcare practitioners. The main objective is to close the communication gap between medical professionals and those looking for quick answers to their health-related questions. The chatbot effectively understands user inputs by analyzing complex language correlations contained in their inquiries by utilizing NLP. Beyond solving the present drawbacks in remote healthcare encounters, this cutting-edge chatbot demonstrates the possibility for predictive diagnosis by spotting patterns in the symptoms that are regularly reported. This idea greatly improves the quality of remote medical consultations by fusing cutting-edge technology with healthcare. Improved patient care and outcomes are made possible by the prompt and accurate responses that are provided.